Establishment of Regional Regulations on Corporate Social Responsibility as an Instrument of Corporate Responsibility for the Protection of Indigenous Peoples - Haliwela, Nancy Silvana; Lakburlawal, Mahrita Aprilya (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This study examines the weak local government supervision of the implementation of Corporate Social and Environmental Responsibility (CSR) by oil and gas mining companies in Eastern Seram Regency, as well as its impact on the indigenous people of the Bati Tribe. The absence of a legal basis in the form of a Regional Regulation on Corporate Social Responsibility (CSR) is the root of the problem that causes suboptimal supervision, indifference to the rights of indigenous peoples, and triggers conflicts related to territories and natural resources. Purposes of the Research: Identify the factors that cause the failure of local government supervision of the implementation of CSR and analyze the urgency of the establishment of a CSR Regional Regulation in order to realize corporate responsibility effectively and fairly for the indigenous peoples of the Bati Tribe. Methods of the Research: The research method used is empirical-juridical with a legal sociological approach and case studies in Eastern Seram Regency. Primary data was obtained through in-depth interviews with indigenous peoples, local governments, and company representatives, as well as field observations. Data analysis was carried out in a thematic qualitative manner to illustrate the relationship between regional policies and CSR practices in the field. Results Main Findings of the Research: The results of the study show that the absence of Regional Regulations on CSR is a crucial factor that paralyzes the supervisory function of local governments. This results in the neglect of indigenous peoples' rights, the lack of CSR contributions that are appropriate, and the increased potential for conflict. This research contributes originality through an in-depth analysis of the case of the Bati indigenous people and the specific identification of the factors of supervisory failure in the region. These findings confirm that the establishment of CSR Regional Regulations is urgent to strengthen the legal basis of supervision, protect the rights of indigenous peoples, and ensure the sustainability of natural resource management.